RULE GAME AND LEARNING DISABILITIES IN SCHOOL CONTEXTS: A CASE STUDY - Saravali, Eliane Giachetto [UNESP]; Zaia, Lia Leme; Gonsalves, erica de Cassia [UNESP] (Inst Fed Education, Science & Technology Of Goias, Campus Inhumas, 2024)
Considering the Brazilian context and aspects inherent to children with complaints of learning difficulties, the central objective of the research was to analyze the effects of a pedagogical intervention with the game of rules Memobox, students referred by their teachers as students with problems in learning. The qualitative case study proved to be adequate for understanding and contextualization of the complaints presented by teachers, as well as the realization and planning of pedagogical interventions based on the equilibration process and developed in the school itself. Participated in the study 17 students aged between 8 and 11 years, enrolled in public school of the state network of S & atilde;o Paulo, submitted to 4 sessions with the game Memobox, organized as follows: learning the game, building strategies, solving situations problem and analysis of the implications on gambling. The sessions lasted, on average, 50 minutes and the children participated in trios or quartets. The analysis of the referrals made by teachers before the sessions, as well as the evaluation they performed after the interventions, indicate progressive improvement in important aspects that often characterize the school complaints, among them, logical reasoning mathematical and textual production, as well as more elementary issues such as recognition of letters, numbers and quantities. This improvement can also be observed during the sessions; little by little the children built new spatial relationships and coordination of different aspects involving the conflicts established in the intervention. There was also improvement in aspects involving social interaction. It is concluded about the importance of the rules game at work with children with difficulties, specifically the importance of Memobox for the construction of basic aspects of cognitive and spatial development.
Keywords: learning difficulties; rules games; intervention